SOCIO-PSYCHOLOGICAL DETERMINANTS OF GENDER RELATIONS IN PUBLIC ADMINISTRATION - Bilosorochka S.I. (Pressing Problems of Public Administration, 2018)
The article reveals the types of human relations according to the degree of openness, their gender relations in public administration of Ukraine are analyzed. Characterization of mansplaining, gaslighting in public administration of Ukraine and their application aspects are given.